Hymenaea stigonocarpa Mart. ex Hayne: A tropical medicinal plant with intestinal anti-inflammatory activity in TNBS model of intestinal inflammation in rats - Orsi, Patricia Rodrigues [UNESP]; Seito, Leonardo Noboru [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Elsevier B.V., 2014)
Ethnopharmacological relevance: Stem bark and fruit pulp of Hymenaea stigonocarpa Mart ex. Hayne (Fabaceae) has been popularly used to treat inflammation and gastrointestinal diseases including ulcers, diarrhea and gastric pain. The aim of this study was to investigate the intestinal anti-inflammatory activity of a methanol extract derived from the stem bark and diet with fruit pulp of Hymenaea stigonocarpa in the TNBS model of intestinal inflammation in rats.Material and methods: The intestinal anti-inflammatory activity of stem bark extract (100, 200 and 400 mg/kg) and fruit pulp (10% and 5% in diet) was measured against the intestinal inflammatory process induced by TNBS (trinitrobenzesulphonic acid) in rats. The protective effects were evaluated as follows: evaluation of intestinal damage (damage score, extension of lesion, colon weight/length ratio), incidence of diarrhea and adherence to adjacent organs, colon glutathione (GSH) and malondialdehyde (MDA) contents, myeloperoxidase (MPO) and alkaline phosphatase (AP) activities. In addition, in vitro studies on lipid peroxidation in rat brain membranes and phytochemical profile were performed with both stem bark and fruit pulp.Results: Treatment with 100, 200 and 400 mg/kg of stem bark extract and 10% fruit pulp flour showed protective effects in the TNBS-induced colon damage, which was related to inhibition of MPO and AP activities, reduction in colon MDA content, and counteraction of GSH depletion induced by inflammatory process. A concentration-dependent inhibitory effect on the lipid peroxidation in rat brain membranes for stem bark and fruit pulp was determined, with an IC50 value of 5.25 +/- 0.23 mu g/mL and 27.33 +/- 0.09 mu g/mL, respectively. Similar phytochemical composition was observed in fruit and stem bark, including mainly flavonoids, condensed tannins and terpenes.Conclusions: Stem bark extract and fruit pulp flour of Hymenaea stigonocarpa prevented TNBS-induced colonic damage in rats and this protective effect were associated to an improvement of intestinal oxidative stress. The observed anti-inflammatory and antioxidant effects may be associated to the presence of flavonoids and tannins in the stem bark and fruit pulp of Hymenaea stigonocarpa. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Hymenaea stigonocarpa; Inflammatory Bowel Disease; Ulcerative colitis; Antioxidant; Flavonoids; Tannins